An analysis on laws regulating fast food / Qayyum Iskandar Sulaiman ... [et al.] - Sulaiman, Qayyum Iskandar; Ahmad, Asyafiqah; Mohd Nasir, Norsyafikah; Yong, Nurul Nabila (Faculty of Law, 2013)
The purpose of this project paper is to focus on the laws administrating the fast food industry. It further moves on to the related ministries on the accessibilities of fast food to consumers and the plans made by the government to promote healthy lifestyle. The study on this area reveals a few of the loopholes in governmental control in the fast food industry. This research paper also lays down several legal remedies that a claimant may invoke against the fast food manufacturers due to the fast food. This study may impact the Faculty of Law of UiTM on the analysis on the legal aspect of fast food industry.